Evolving trends in dental education: a bibliometric analysis of research outputs, challenges and innovations (1991–2023) - Yuh-Shan Ho; Essam Ahmed Al-Moraissi; Nikolaos Christidis; Maria Christidis (Cogent Education)
This bibliometric analysis aimed to investigate research trends and publication performance in dental education, incorporating article titles, author keywords, Keywords Plus and abstracts. Data were retrieved on 22 June 2024 from the Science Citation Index Expanded (SCI-EXPANDED) for studies published between 1991 and 2023. Research trends were analyzed through keyword distributions in titles and author-selected keywords. The search identified 4,270 documents in SCI-EXPANDED, with 3,483 categorized as ‘articles,’ published in 249 journals. Key findings revealed ‘dental students,’ ‘assessment,’ ‘curriculum’ and ‘clinical education’ as the most common keywords. The most-cited study, authored by Douglass et al. (2002), originated in the USA. The USA and UK led in publication volume, reflecting their strong traditions in higher professional education and use of English. Most publications were single-country studies, as research on dental education, curriculum and assessment tends to have a local focus. From 1991 to 2023, research centered on the academic environment in dental education, digital tools and the impact of the COVID-19 pandemic. This study’s novel inclusion of Keywords Plus and abstract analysis enhanced understanding of research trends and citation patterns in dental education. In conclusion, research reflects evolving academic needs, highlighting both local specificity and global influences on dental education.